The Extractive Corruption in Colombia 2000 to 2011 (2019)
What is the impact of the incomes from natural resources extraction in the investigation related with corruption in Colombia? We constructed a balanced panel for 1091 municipalities with information from 2000 to 2011, and through a Dif-Dif methodology we found opposite and significant effects in the municipalities that produced the main natural resources extracted in Colombia: oil and coal. On the one hand, a raise of 1% in the international price of oil increased in 11% the average number of investigation related with corruption. On the other hand, a raise in 1% on the international price of coal reduced in 1.5% the average number of cases related with corruption investigated by PGN.